Conservative Management of Cesarean Scar Pregnancy: A Case Report and Literature Review - Manuel Sánchez-Prieto; María Jesús Puy; Núria Barbany; Betlem Graupera; Maria Angela Pascual; Pere Barri-Soldevila (Case Reports in Obstetrics and Gynecology)
Cesarean scar pregnancy (CSP) is a rare form of ectopic pregnancy located in the lower uterine segment. The current increase in the percentage of cesarean sections is accompanied by significant growth in the incidence of CSP, while advances in ultrasound diagnostic techniques have led to a greater number of CSP diagnoses. A misdiagnosed CSP, or one that is diagnosed too late, is life-threatening to the pregnant patient and predisposes her to complications such as uterine bleeding or rupture, which often require hysterectomy and thus result in the irreversible loss of fertility. We present the case of a 50-year-old woman with a history of undiagnosed CSP after multiple consultations for intermittent bleeding and hemorrhage. She was diagnosed by ultrasound and the diagnosis was confirmed by hysteroscopy. She underwent conservative medical treatment that was successful.